Camurati-Engelmann disease: review of the clinical, radiological, and molecular data of 24 families and implications for diagnosis and treatment. Issue 1 (13th May 2005) - Janssens, K; Vanhoenacker, F; Bonduelle, M; Verbruggen, L; Van Maldergem, L; Ralston, S; Guañabens, N; Migone, N; Wientroub, S; Divizia, M T; Bergmann, C; Bennett, C; et al.
Abstract : Camurati-Engelmann disease (CED) is a rare autosomal dominant type of bone dysplasia. This review is based on the unpublished and detailed clinical, radiological, and molecular findings in 14 CED families, comprising 41 patients, combined with data from 10 other previously reported CED families. For all 100 cases, molecular evidence for CED was available, as a mutation was detected in TGFB1, the gene encoding transforming growth factor (TGF) β1. Pain in the extremities was the most common clinical symptom, present in 68% of the patients. A waddling gait (48%), easy fatigability (44%), and muscle weakness (39%) were other important features. Radiological symptoms were not fully penetrant, with 94% of the patients showing the typical long bone involvement. A large percentage of the patients also showed involvement of the skull (54%) and pelvis (63%). The review provides an overview of possible treatments, diagnostic guidelines, and considerations for prenatal testing. The detailed description of such a large set of CED patients will be of value in establishing the correct diagnosis, genetic counselling, and treatment.